Implementasi Role Playing dalam Meningkatkan Hasil Belajar dan Keterampilan Sosial Siswa pada Pembelajaran PAI di Sekolah Dasar - Liana Sari, Devi; Suriana, Suriana (Tarbiyatuna Kajian Pendidikan Islam, 2026)
In order for students to achieve appropriate learning outcomes and social skills, it is very important to apply teaching models that are relevant to the subject matter. Unfortunately, educators often fail to consider the suitability of the models and educational resources they use. The purpose of this study was to determine how the use of role-playing learning models can improve students' social skills and learning outcomes in Islamic Religious Education (PAI) subjects in elementary schools. Kurt Lewin's classroom action research methodology, which consists of two cycles of planning, implementation, observation, and reflection, was used in this study. Data were collected and analyzed through data collection, data reduction, and conclusion drawing. The findings indicate that the use of the role-playing learning paradigm with congregational prayer material significantly improves learning outcomes and social skills. This can be seen in the first cycle where role playing was not yet utilized in learning, only two students (10%) had learning outcomes above the minimum passing grade. The remaining 18 students (90%) still did not achieve satisfactory results, as did the students' social skills, which were not yet apparent and tended to be inadequate. Then, after the implementation of cycle 2 with the application of role playing, student learning outcomes improved with only one student (5%) not passing the minimum passing grade. Students' social skills also improved with the existence of cooperation between students, mutual respect, empathy, willingness to do role playing, and acceptance of feedback from teachers.